2009
DOI: 10.1111/j.1471-4159.2009.06283.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ versus extracellular effects of microglia‐derived cysteine proteases in a conditioned medium transfer model

Abstract: Activated microglia release inflammatory mediators that display either beneficial or harmful effects on neuronal survival and signaling. In the present study we demonstrate that exposure to lipopolysaccharide leads to an increase in the lysosomal cysteine proteases, cathepsin B, K, S, and X, in culture supernatants of the microglia cell line BV‐2. In addition, we observed an up‐regulation of cathepsins in the cytoplasmic fraction in response to stimulation with lipopolysaccharide. Conditioned medium from these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…Using the murine N-13 microglial cell line, one study reported that LPS decreased Cat S cellular levels and activity but increased its secretion [58], and another showed that basic fibroblast growth factor increased both intra- and extracellular Cat S activity [54]. In the BV-2 microglia cell line, LPS increased intracellular levels of Cat S and Cat X but evoked secretion of Cat -B, -K, -S and -X [61]. Interestingly, co-stimulation of the P2X7 purinergic receptor was necessary for secretion of enzymatically active Cat S from LPS-treated rat primary microglia [62].…”
Section: Discussionmentioning
confidence: 99%
“…Using the murine N-13 microglial cell line, one study reported that LPS decreased Cat S cellular levels and activity but increased its secretion [58], and another showed that basic fibroblast growth factor increased both intra- and extracellular Cat S activity [54]. In the BV-2 microglia cell line, LPS increased intracellular levels of Cat S and Cat X but evoked secretion of Cat -B, -K, -S and -X [61]. Interestingly, co-stimulation of the P2X7 purinergic receptor was necessary for secretion of enzymatically active Cat S from LPS-treated rat primary microglia [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, in several neuropathologies, where chronic inflammation is present, the inflammatory products derived from activated microglia may also promote neurodegeneration and contribute to neuronal loss (Gonz alez-Scarano & Baltuch, 1999). In addition to inflammatory cytokines, activated microglia secretes lysosomal proteases, the cathepsins, including cathepsin X (Nakanishi, 2003;Wendt et al, 2009). Cathepsin X expression and proteolytic activity were strongly upregulated in the mouse brain, in particular in glial cells and aged neurons, and its association with senile plaques was also observed (Wendt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The lysosomal cysteine protease, cathepsin Z, has been reported to be highly expressed in antigen presenting cells (APCs) [12, 13, 34]. This was confirmed in peritoneal and bone marrow-derived macrophages (pMØ, BMMØ), immortalized and bone marrow-derived dendritic cells (DC2.4, BMDC) and immortalized microglia (BV2) (Fig.…”
Section: Resultsmentioning
confidence: 80%